Same Country; Same Lands; 78 Countries Away: An exploration of the nature and extent of collaboration between the Voluntary Sector and First Nations Child and Family Services Agencies in British Columbia - Blackstock, Cindy (First Peoples Child & Family Review, 2005)
As the United Nations Committee on the Rights of the Child (2003) noted, Aboriginal children face more discrimination and increased risk factors than other Canadian children. Their lived experiences are shaped by the policies of assimilation and colonization that aimed to eliminate Aboriginal cultures through repression of fundamental freedoms, denial of ownership and the operation of residential schools (RCAP, 1996; Milloy, 1999). First Nations child and family service agencies have expressed concern about the lack of resources available to support families in redressing the significant impacts of colonization. The voluntary sector provides a myriad of important social supports to Canadians off reserve and this research project sought to determine how accessible voluntary sector resources were for First Nations children, youth and families resident on reserve in British Columbia. Results of a provincial survey of First Nations child and family service agencies and child, youth and family voluntary sector organizations indicate very limited access to voluntary sector services. Possible rationales for this social exclusion are examined and recommendations for improvement are discussed.